2022
DOI: 10.55047/marginal.v1i4.302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dividend Policy and Macroeconomics on Stock Prices

Abstract: This study analyzes the Effect of Dividend Policy and Macroeconomics on Stock Prices. Dividend Policy is calculated using the Dividend Payout Ratio (DPR), while Macroeconomics is proxied by inflation, interest rates, and exchange rates, and the Stock Price is measured by the closing price. The population in this study is all manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange in 2016-2020. The technique used in this study was purposive sampling with five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Dutrianda & Pangaribuan (2020) states that "companies are highly dependent on the capacity to manage intangible assets in order to survive in the competition". Several studies have also concluded that there has been a decrease in the value relevance of accounting information as a result of an increase in unreported intangible assets (Simajuntak, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Dutrianda & Pangaribuan (2020) states that "companies are highly dependent on the capacity to manage intangible assets in order to survive in the competition". Several studies have also concluded that there has been a decrease in the value relevance of accounting information as a result of an increase in unreported intangible assets (Simajuntak, 2022).…”
Section: Introductionmentioning
confidence: 99%